Effects of A Self – Efficacy Promoting Program on Caring for Pre-Hypertension Group among Community Health Volunteers - Sonthitham, Kirananan; Chamusri, Somsaowanuch (Journal of The Royal Thai Army Nurses, 2020)
This quasi-experimental research was to examine the effectiveness of perceived self-efficacy promoting program on caring for pre-hypertension group among community health volunteers, using one group pre-posttest design. The sample consisted of 41 community health volunteers. The instrument of this research consisted of a handbook of a perceived self-efficacy among community health volunteers on caring for pre-hypertension group, risk factor of hypertension assessment form and handbook for advising of caring themselves to pre-hypertension group, using the self-efficacy theory of Bandura (1997) included 1) Mastery experiences 2) Vicarious experiences 3) Verbal persuasion and 4) Emotional and physiological states. Data were analyzed by using percentage, mean, standard deviation, and dependent t-test. The results revealed that self-efficacy on caring for pre-hypertension group among community health volunteers was higher than before receiving the program at the statistical level of 0.01. Therefore, nurses should apply this program to use on caring for pre-hypertension group.